Agent Banking And Poverty Reduction In Benue State, Nigeria - Akighir, David Terfa; Tyagher, T. Jacob; Ateata, Aaron (Advances in Social Sciences Research Journal, 2020)
The study investigated the impact of agent banking on poverty reduction in Benue State, Nigeria. The study is hinged on the agency theory, risk management theory, the regulatory dialectic theory and the basic needs theory. Focusing on the agent banking activities of the First bank PLC, the study used the Taro Yammene’s formula to select 199 agents for investigation. Questionnaire was used for data collection but only 185 copies of the questionnaire were retrieved for analysis. The study employed descriptive tools such as tables and percentages and paired t-test as well as Foster, Greer and Thornbecke (FGT) index. Also, a logit regression model was employed to ascertain whether or not agent bank has the probability of reducing poverty in Benue State. The study found that engaging in agent banking has the probability of reducing poverty in Benue State which is typically an agrarian state with high poverty incidence among highly unbanked population. Agent banking in this unbanked State where only 11 local government areas out of 23 local government areas have the presence of banks has the potential of increasing financial inclusion and enhancing financial literacy. With the presence of agent banking in the state, it will enhance business sustainability and facilitate financial transactions. These will increase economic activities and increase employments and reduce poverty. Given the potentials of agent banking for socio-economic development in the state, it is recommended that financial literacy awareness should be created so that rural population who have long lived unbanked to accept banking services via the agent banking. Also, banks operating in the state should leverage on the opportunity of agent banking to penetrate the rural population with a view to achieving financial inclusion in line with the CBN’s revived National Financial Inclusion Strategy (NFIS) which places implementation focus on women, rural areas, youth, Northern Nigeria and MSMEs to achieve 95% financial inclusion rate by 2024.